Photonic composite materials from cellulose nanorods and clay nanolayers - Trindade, Ana C. (2021)
POCI-01-0145-FEDER007688 (Reference UID/CTM/50025) PTDC/FIS-NAN/0117/2014 PTDC/CTM-BIO/6178/2014 M-ERA-NET2/0007/2016 (CellColor) PTDC/CTM-REF/30529/2017 (NanoCell2SEC). {Nano2021 Program (250619 Graphene-NanoClay Systems).